Vascular responses of penetrating vessels during cortical spreading depolarization with ultrasound dynamic ultrafast Doppler imaging - Hsieh, Bao-Yu; Kao, Yu-Chieh Jill; Zhou, Ning; Lin, Yi-Pei; Mei, Yu-Ying; Chu, Sung-Yu; Wu, Dong-Chuan (Frontiers in Neuroscience, 2022)
The dynamic vascular responses during cortical spreading depolarization (CSD) are causally related to pathophysiological consequences in numerous neurovascular conditions, including ischemia, traumatic brain injury, cerebral hemorrhage, and migraine. Monitoring of the hemodynamic responses of cerebral penetrating vessels during CSD are motivated to understand the mechanism of CSD and related neurological disorders. Six SD rats were used, and craniotomy surgery was performed before imaging. CSDs were induced by topical KCl application. Ultrasound dynamic ultrafast Doppler was used to access hemodynamic changes, including cerebral blood volume (CBV) and flow velocity during CSD, and further analyzed those in a single penetrating arteriole or venule. The CSD-induced hemodynamic changes with typical duration and propagation speed were detected by ultrafast Doppler in the cerebral cortex ipsilateral to the induction site. The hemodynamics typically showed triphasic changes, including an initial hypoperfusion, prominent hyperperfusion peak, followed by a long-period depression in CBV. Moreover, different hemodynamics between individual penetrating arterioles and venules were proposed by quantification of CBV and flow velocity. The negative correlation between the basal CBV and CSD-induced change was also reported in penetrating vessels. These results indicate specific vascular dynamics of cerebral penetrating vessels and possibly different contribution of penetrating arterioles and venules to the CSD-related pathological vascular consequences. We proposed for the first time using ultrasound dynamic ultrafast Doppler imaging to investigate CSD-induced cerebral vascular responses. With this imaging platform, it has potential to monitor the hemodynamics of cortical penetrating vessels during brain injuries to understand the mechanism of CSD in advance.